2000
DOI: 10.1023/a:1005263601964
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A survey of sheep and goat producers in the state of Maharashtra, India, was undertaken to ascertain the extent and economic impact of sheep pox and goat pox (SGP). One thousand one hundred and sixteen owners were interviewed. Eighty owners (7.2%) reported that they had experienced an outbreak of the disease in the previous 6 years. The results showed that, while producers ranked SGP below other infectious diseases such as foot-and-mouth disease, rinderpest and enterotoxaemia, when SGP occurred it had a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 1 publication
3
14
2
Order By: Relevance
“…Seven out of every 10 farmers reported they had not replaced animals that died, were sold or slaughtered as a consequence of the outbreak. Price reduction on affected cattle has been reported in India and Ethiopia (1,2). In comparison to the current study, a similar price reduction was reported in India (farmers reported losing around 50% of the market value when selling affected cattle), while in Ethiopia the reported loss was due to a reduction in beef production.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Seven out of every 10 farmers reported they had not replaced animals that died, were sold or slaughtered as a consequence of the outbreak. Price reduction on affected cattle has been reported in India and Ethiopia (1,2). In comparison to the current study, a similar price reduction was reported in India (farmers reported losing around 50% of the market value when selling affected cattle), while in Ethiopia the reported loss was due to a reduction in beef production.…”
Section: Discussionsupporting
confidence: 87%
“…This study quantifies the direct production losses and additional costs that subsistence farmers incur as a consequence of the three CPPV diseases in Nigeria, and identifies coping strategies that might be playing a role in virus transmission. This work builds on previous studies investigating the impact of CPPV disease on livestock in different settings (1,2,9,26). The results from this study suggest that LSD, SP, and GP have an immediate as well as potentially long lasting impacts on subsistence farmers' livelihoods with important differences between production systems.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…CaPV isolates are shown to have differential host preference demonstrated by experimental challenge studies and virus isolation [4] and considered as different entities within the Indian subcontinent [5]. Capripox is enzootic in Southwest and Central Asia, Northern and Central Africa and Indian subcontinent [1] and pose potential economic threat to the small ruminant industry [6].…”
mentioning
confidence: 99%